2022
DOI: 10.1007/s00167-022-06881-z
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular labral tear is associated with high pelvic incidence with or without femoroacetabular impingement morphology

Abstract: Purpose The aim of this study was to investigate the association between pelvic sagittal parameters and acetabular labral tears. Methods Three-hundred and sixty-five patients (449 hips) who underwent magnetic resonance imaging (MRI) or magnetic resonance arthrogram (MRA) for hip pain were enrolled in this study. Pelvic sagittal parameters, including the pelvic incidence, pelvic tilt, and sacral slope, were measured with a standing lumbosacral lateral radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…2,23,52,54 Additionally, spine users may compensate by posteriorly tilting their pelvis; however, this maladaptive postural response effectively causes functional undercoverage of the femoral head anteriorly, thereby creating a more verticalized articular loading surface of the acetabulum. 13,23,24,27,48 Even in the absence of FAI, previous literature has suggested that the deleterious loading of the anterior acetabulum may be the impetus for acetabular labral tears, nontraumatic femoral head collapse, and accelerated rates of osteoarthritis. 14,23,24,54 Thus, impingement may not be the primary driver of symptoms for all patients with FAI, but rather the resulting compensatory adjustments seen in the setting of high PI could underlie the relatively worse functional outcomes observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,23,52,54 Additionally, spine users may compensate by posteriorly tilting their pelvis; however, this maladaptive postural response effectively causes functional undercoverage of the femoral head anteriorly, thereby creating a more verticalized articular loading surface of the acetabulum. 13,23,24,27,48 Even in the absence of FAI, previous literature has suggested that the deleterious loading of the anterior acetabulum may be the impetus for acetabular labral tears, nontraumatic femoral head collapse, and accelerated rates of osteoarthritis. 14,23,24,54 Thus, impingement may not be the primary driver of symptoms for all patients with FAI, but rather the resulting compensatory adjustments seen in the setting of high PI could underlie the relatively worse functional outcomes observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…42,48 As a result, patients with low PI often attempt to maintain sagittal alignment and a normal degree of lumbar lordosis by anteriorly tilting the pelvis (ie, decreasing PT). 23,52,54 This anterior tilt of the pelvis may impose overcoverage of the anterosuperior acetabulum and reduced flexion at the hip joint, a hallmark of symptomatic FAI. Although the etiopathogenesis of FAI remains highly debated, studies have gone further to suggest that cam deformities may be directly associated with decreased PI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pelvic incidence is calculated as the sum of the pelvic tilt and sacral slope and, thus, is a position‐independent anatomical parameter of sagittal plane spinopelvic balance, with the normal range of 35 − 85° [18]. Several studies have previously shown that the pelvic incidence is associated with the development of spondylolisthesis [29], hip osteoarthritis [8], progression in osteonecrosis of the femoral head [15], and acetabular labral tear [16]. Consistent with the current study (Fig.…”
Section: Discussionmentioning
confidence: 99%